Relationship between price-earnings ratios and expected return of common stocks: The case of Malaysia - Ismail Ibrahim,; Othman Yong, (Penerbit Universiti Kebangsaan Malaysia, 1991)
This paper investigates the relationship between PIE ratio of a stock and its expected return. Spearman rank correlatiOn, a nonparametric test, was used to test this relationship. ThIs study found significant relatIOnship between the two for the entire period 1980 to 1989 and for the sub-period 1980 101984, which suggest that the market for MalaYSia stocks IS not efficient In the semi-strong form of the efficient market hyporhesis (EMH). However, for the sub-period 1985 to 1989, the relationship is not significant.